A case of anomalous right coronary artery from the pulmonary trunk, aortopulmonary window, and interrupted aortic arch type a in a term neonate - Ahlam Salim Atiq; Madan Mohan Maddali; Salim Nasser Al-Maskari; Faiza Abdullah Al Kindi; Sunny Zacharias (Annals of Pediatric Cardiology)
We report a case of a term neonate presenting with anomalous origin of the right coronary artery from the pulmonary trunk, an aortopulmonary window, interrupted aortic arch type A, and an atrial septal defect within the oval fossa. The infant, admitted in cardiogenic shock, was stabilized with fluid resuscitation, intubation, and inotropic support. Comprehensive imaging revealed the complex cardiac anomalies. Surgical intervention successfully addressed all the lesions. The patient showed excellent postoperative recovery, with no complications at 6 months. Our experience underscores the critical need for detailed preoperative assessment in managing complex congenital heart defects.